Development of Lean Assessment Tools Dimensions and Indicators For SMEs in Indonesia - David Dwi Harjanto; Putu Dana Karningsih (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2021)
In advance, the lean concept was used and applicated for big manufacturing industry. However, the lean concept used widely for all kinds of industry in the world. The improvement practice as lean and JIT also used for small industry (SMEs) in any countries which have implemented lean. The SMEs which have implemented lean showed any improvement, as the increasing of efficiency and flexibility, clear of communication and close with the Customers so the response and feedback are quicker and the costs are lower. The lean assessment tools used to value the effectiveness and the efficiency from lean implementation in the certain industry. The development of lean assessment tool for SMEs done by considering the difference between SMEs characteristic with industry a big scale. Have been many studies development of lean assessment to measure lean implementation in manufacturing industry and service generally without considered the size of his industry. However there are just a few development of lean assessment tools study that specific to measure the implementation lean manufacturing on SMEs. Therefore, this study aims to collect and compare the dimensions and indicators of the Lean Assessment Tool from several countries that are suitable for use in manufacture SMEs in Indonesia.